Study on The Development of A Marine Tourism Potential in Kodingareng Keke Island in Makassar - Sutomo, Didit Darmawan; Rauf, Abdul; Kasnir, Muh. (FAPETKAN UNTAD, 2019)
This study aimed to determine the potential diversity of the coral reef and coral reef fish ecosystems of Kodingareng Keke Island and the development strategies and priorities of Kodingareng Keke Island as a marine tourism destination. This research used purposive sampling with 50 respondents, coral data collection method used was Line Intercept Transect (LIT) with transect line length of 50 meters and depth of 5 meters, method used to obtain coral reef fish data was Underwater Visual Census (UVC). The result of analysis showed that the average coral ranged from 63,6% to 77,8% and the average abundance of fish at 3 observation stations, namely station I (17,65%), station II (14,78%) and station III (18,67%), thus it can be conculded that this location is feasible for snorkeling and diving tourism. The priority programs for the development of the marine tourism area of Kodingareng Keke Island include increasing supervision, creating periodical Object Development Master Plans (RIPO), implementing local regulations on the use of coastal resources, involving local communities, the general public and the government in nature conservation activities, setting labor standards, and improving the quality of local human resources through training.Keywords: Coral reef, Coral reef fish, Tourism.